Pengembangan Media E - Komik dalam Pembelajaran PAI Berbasis Kontekstual Materi Kisah Sahabat Rasulullah SAW Kelas 5 SDN Plumbungan Sukodono Sidoarjo - Mariana, Dielfi (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
E-Comics are a learning tool that can facilitate student learning due to the lack of learning media used by educators due to limited ability to create interesting learning media. The absence of e-comic media regarding the story of the Prophet's companions at Plumbungan Elementary School has motivated researchers to develop e-comic media in contextual-based PAI learning so that the desired learning objectives are achieved. This study carries out a form of research (Borg & Gall), researchers practice and modify, this research and development stage can be simpler and easier to understand. The types of data used are qualitative and quantitative data. From the score data obtained, it is a very interesting criterion. The results obtained from the practicality test of Koma products were obtained from teacher response questionnaires ('94.82%) and student responses (84.61%). These data show that the results of the criteria are very practical. Comic book products obtained effective criteria results and there was also an increase in teacher learning activities and student activities before and when using e-comic media, namely student activity before 46.75% to 89.28% while teacher activity before using the product was 74.43%. to '90.27% so it can be concluded that e-comic media in contextual, PAI-based learning is very effective in increasing teacher and student activity in the learning process. Based on these results, e-comic media in contextual-based PAI learning for Grade 5 elementary schools has met the requirements for use in learning because it has met the criteria of valid, interesting, effective and practical.